A Student Pharmacist Quality Engagement Team to Support Initial Implementation of Comprehensive Medication Management within Independent Community Pharmacies - Sophia M. C. Herbert; Joni C. Carroll; Kim C. Coley; Stephanie Harriman McGrath; Melissa Somma McGivney (MDPI AG, 2020)
In 2017, the Pennsylvania Pharmacists Care Network (PPCN), an enhanced pharmacy services network, and STRAND Clinical Technologies partnered to launch a payor contract with a Pennsylvania Medicaid Managed Care Organization for the provision of comprehensive medication management (CMM) at PPCN pharmacies. PPCN and the Community Leadership and Innovation in Practice Center at the University of Pittsburgh School of Pharmacy partnered to create the Quality Engagement Team (QET), a group of student pharmacists formed with the intent to support the initial implementation of this contract. The QET supported the pharmacies through biweekly phone calls, which led to increased pharmacist engagement and produced impactful patient encounter stories that were then reported back to the payor. We utilized Active Implementation Frameworks and select implementation strategies from the Expert Recommendations for Implementing Change project throughout the implementation period. The QET supported the successful implementation of this payor contract, which saw an increase in CMM encounters completed by the pharmacists during each month of the four-month contract period. Students, pharmacists and the payor each derived meaningful benefits from this initiative. Student pharmacists can be a powerful asset in the implementation of payor programs within an enhanced pharmacy services network, resulting in the mutually beneficial and sustainable support of the network.